Orchid diversity across different forest types on Mt. Malindang, Philippines - YUNALYN LABAJO-VILLANTES; JIM COOTES; YI-BO LUO; OLGA M. NUNEZA (Society for Indonesian Biodiversity, 2024)
Abstract. Labajo-Villantes Y, Cootes J, Luo Y-B, Nuneza OM. 2024. Orchid diversity across different forest types on Mt. Malindang, Philippines. Biodiversitas 25: 605-615. Mt. Malindang Range Natural Park is one of the most significant biodiversity and conservation areas and is considered a biodiversity hotspot. There have been many biodiversity studies on Mt. Malindang, but information on orchid taxonomy and distribution is limited. This study aimed to conduct a comprehensive inventory of orchids using an exploratory method. Samplings were conducted in different forest types: montane, mossy, dipterocarp, mixed dipterocarp, and almaciga. A total of 114 orchid species with 55 endemics were recorded. Three of these (Phalaenopsis x intermedia Lindl., Paphiopedilum hennisianum (M.W.Wood) Fowlie, and Paphiopedilum haynaldianum (Rchb.f.) Stein) were under Appendix I (can only be exported under specific circumstances). At the same time, 78 were under the Appendix II (follow controlled trades) categories of the Convention on International Trade in Endangered Species of Wild Fauna and Flora. P. hennisianum and P. haynaldianum, listed as endangered species globally, were observed in montane and mossy forests, respectively. Among the six sampling sites, the montane forest was the most species-rich, with the most endemics, followed by the mossy forest. Almaciga and mixed dipterocarp forests were closely related with 100% similarity. The results of this study are valuable to Mt. Malindang's ecological profile for more effective protection and conservation plans.